Óleo de Copaíba na cicatrização de feridas experimentais em cavalos - Lucas, Flavia de Almeida [UNESP]; Kandrotas, Adriana Lima [UNESP]; Neto, Eugenio Nardin [UNESP]; de Siqueira, Carlos Eduardo [UNESP]; André, Gabriela Santo [UNESP]; Bromerschenkel, Ingrid [UNESP]; Perri, Silvia Helena Venturoli [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the effects of 10% copaiba oil in experimentally induced wounds in horses. Four wounds were made in the lumbar and metacarpal regions of eight adult horses. In the treatment group, the wounds received 10% copaiba oil and in the control group 0.9% sodium chloride, in the daily dressing for 21 days. The wounds were evaluated three, 7, 14, and 21 days postoperatively. No significant differences were observed between the groups. The mean lumbar wound contraction rates were 80.54% and 69.64%, for the control and treated groups, respectively. For the wounds in the metacarpal region, these averages were 44.15% and 52.48%, respectively. Under the experimental conditions of the present study, it is concluded that 10% copaiba oil has beneficial in wound healing in the equine species and suggest that copaiba oil can be used as a therapeutic possibility in equine wound therapy.
Copaiba oil in experimental wound healing in horses
Keywords: Equine; Phytotherapy; Wound healing